Car Thief Shot Dead After 3 Hour Pursuit - New Straits Times, Fadhal A. Ghani & Lee Shi-Lan (2008)
A police ambush on Wednesday night turned into a Hollywood action movie scene after a car thief stole a patrol car and rammed into 3 vehicles while trying to flee from the police during a three-hour pursuit.